2019
DOI: 10.2109/jcersj2.19042
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate apatite bone replacement: learn from the bone

Abstract: Bone is not composed of hydroxyapatite (HAp), but of carbonate apatite (CO 3 Ap). Although the decomposition of CO 3 Ap begins at around 400°C, and thus, the fabrication of CO 3 Ap blocks by sintering is difficult, CO 3 Ap blocks have recently been fabricated via a dissolutionprecipitation reaction in Na 2 HPO 4 solution using a CaCO 3 block as a precursor. Compared to sintered HAp, which is not resorbed by osteoclasts, CO 3 Ap is resorbed by osteoclasts. Furthermore, CO 3 Ap upregulates the differentiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 11 publications
0
60
0
1
Order By: Relevance
“…The CAp coatings enhanced the ALP expression level from osteoblast cells comparable to the HAp coating as shown in Figure 9(a). An increase of ALP expression of osteoblast cells is generally accompanied by an increase of the expression of osteoblastic differentiation markers such as type I collagen, osteopontin and osteocalcin on CAp, sintered HAp, Ti and zirconia surfaces [21,36,37]. With an increase of culture period, calcium phosphate particles with a diameter of several micrometers increased on the CAp-and HAp-coated surfaces (Fig.…”
Section: Effect Of Cap Coating On Bone Formation Ability Of Osteoblastsmentioning
confidence: 92%
See 3 more Smart Citations
“…The CAp coatings enhanced the ALP expression level from osteoblast cells comparable to the HAp coating as shown in Figure 9(a). An increase of ALP expression of osteoblast cells is generally accompanied by an increase of the expression of osteoblastic differentiation markers such as type I collagen, osteopontin and osteocalcin on CAp, sintered HAp, Ti and zirconia surfaces [21,36,37]. With an increase of culture period, calcium phosphate particles with a diameter of several micrometers increased on the CAp-and HAp-coated surfaces (Fig.…”
Section: Effect Of Cap Coating On Bone Formation Ability Of Osteoblastsmentioning
confidence: 92%
“…The degradation of the CAp coatings in the acidified microenvironment formed by osteoclasts should have allowed the access of acidified fluid to substrate WE43, leading to the corrosion localized under the cell bodies. Since HAp shows much lower solubility than CAp at pH 3-5 [21], the dissolution of the HAp coating did not occur under the cell bodies. It is thus demonstrated that the CAp coatings formed on WE43 can be degraded by microenvironmental acidification in the osteoclastic resorption mechanism.…”
Section: Osteoclastic Resorption Of Cap Coatings and Its Effect On Camentioning
confidence: 99%
See 2 more Smart Citations
“…The fabricated CO 3 Ap block thus shows properties similar to the properties of the bone. In contrast to sintered HAp, which is not resorbed by osteoclasts, CO 3 Ap blocks are resorbed by osteoclasts and they can serve as a new bone replacement [9,29,30,31]. Furthermore, CO 3 Ap blocks were found to upregulate osteoblastic differentiation and they showed a much higher osteoconductivity than HAp [32].…”
Section: Introductionmentioning
confidence: 99%